Women's perceptions of their right to choose the place of childbirth: a qualitative study - Papadopoulos, Irena; Martenson, Lena B.; Papastavrou, Evridiki; Kouta, Christiana; Hadjigeorgiou, Eleni (My University, 2012)
OBJECTIVE: To explore Greek Cypriot women's perceptions of their right to choose the place of childbirth. DESIGN: This study is qualitative and is based on Husserl's phenomenological approach. The field work extended over a 6-month period in 2010–2011. SETTING: In all cities of the Republic of Cyprus. PARTICIPANTS: Purposive sample of 55 women within 1 year after birth. Forty-eight women were recruited for semistructured interviews and six of them took place in first focus group. The second group consisted of seven women that did not participate in interviews. RESULTS: Women's perceptions were categorized into four themes: (a) informed choice for birth place, (b) trusting relationship with health professionals, (c) medicalization of childbirth, and (d) safety of the mother and baby. CONCLUSIONS: There is no equity and accessibility in Cyprus maternity care system because it does not provide correct information and accessibility to all birthplace choices. This study demonstrated the need to explore women's views before formulating policy for maternity care. These views will be helpful for the creation of an innovative evidence-based maternity care policy, taking into account women's needs, and will be helpful to raise awareness among health professionals for maternity care improvement. IMPLICATIONS FOR PRACTICE: Ensuring the right for birthplace choices is a social and political necessity that enhances the existing health care systems and health professionals to provide quality and holistic maternity care. Conducting more studies on maternity care in Cyprus will reinforce the aim for improving the health of the women, neonates, and society.
Keywords: Place of birth; Informed choices; Hospital birth; Home birth; Birth center; Medical model